2015
DOI: 10.1002/smll.201501381
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dimensional Topological Crystalline Insulators

Abstract: Topological crystalline insulators (TCIs) are recently discovered topological phase with robust surface states residing on high-symmetry crystal surfaces. Different from conventional topological insulators (TIs), protection of surface states on TCIs comes from point-group symmetry instead of time-reversal symmetry in TIs. The distinct properties of TCIs make them promising candidates for the use in novel spintronics, low-dissipation quantum computation, tunable pressure sensor, mid-infrared detector, and therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Soon after the discovery of SnTe a bulk TCI, several methods to grow SnTe nanostructures by vapor transport with Ar gas flow with/without a gold catalyst were reported [31][32][33][34][35][36]. These suggested that In-SnTe nanostructures can be made available with similar growth methods.…”
Section: Introductionmentioning
confidence: 99%
“…Soon after the discovery of SnTe a bulk TCI, several methods to grow SnTe nanostructures by vapor transport with Ar gas flow with/without a gold catalyst were reported [31][32][33][34][35][36]. These suggested that In-SnTe nanostructures can be made available with similar growth methods.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction was then immediately confirmed by other three groups through angle‐resolved photoemission‐spectroscopy (APRES) in 2012 . Compared with TIs, TCIs exhibit three intriguing features: (1) they are of highly symmetry crystal structures, (2) gapless metallic states only reside on those mirror‐symmetry surfaces such as (100), (111), and (110), (3) Dirac cones on TCIs surface can be opened up by breaking symmetry, manipulating temperature, and tailoring compositions . For example, as shown in Figure b and c, there will be a non‐trivial to trivial topological phase transition while continuously varying the composition of Pb 1‐ x Sn x Te or changing the temperature tested.…”
Section: Applicationsmentioning
confidence: 77%
“…Up to now, a variety of non‐layered materials have been synthesized successfully into 2D structures, including metals, metal oxides, metal chalcogenides, topological crystalline insulators, organic‐inorganic hybrid perovskites, and others. With this special 2D geometry, they have been studied as photodetectors, low‐dissipation logic devises, catalysts for water splitting and CO oxidation, and electrodes for Li‐ion batteries etc.…”
Section: Materials Category Synthesis Mechanism and Methodsmentioning
confidence: 99%
See 2 more Smart Citations